Odpowiedzi

2010-02-02T17:08:40+01:00
A) 3x(1/2 - 2y + 6)=
1½x -6xy +18x

b) 2ab (a - 2b + 3)=
2a²b-4ab² +6ab

c) ( 2x - 4y - 3xy + 1 ) * (-3xy) =
-6x²y-12xy²+9x²y² -3xy

d) 1/4 abc * (4a - 8b + 12c - 8 ) =
a²bc -2ab²c +3abc² -2abc

e) 2* ( x -3) + 3 * (x + 1 ) =
2x-6 +3x+3 = 5x -3

f) -3 * ( 2x - 4y ) - ( x - 3y ) =
-6x +12y -x +3y= -7x +15y
2010-02-02T17:10:04+01:00
A) 3x(1/2 - 2y + 6)=3/2 x -6xy+18x=19 i 1/2 x -6xy
b) 2ab (a - 2b + 3)=2a²b-4ab²+6ab
c) ( 2x - 4y - 3xy + 1 ) * (-3xy) =-6x²y+12xy²+9x²y²-3xy
d) 1/4 abc * (4a - 8b + 12c - 8 ) =a²bc-2ab²c+3abc²-2abc
e) 2* ( x -3) + 3 * (x + 1 ) =2x-6+3x+3=5x-3
f) -3 * ( 2x - 4y ) - ( x - 3y ) = -6x+12y-x+3y=-7x+15y